2019
DOI: 10.1002/jso.25464
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk evaluation for pancreatic fistula after pancreaticoduodenectomy

Abstract: Background Pancreatic fistula remains common, with limited ability to risk stratify patients preoperatively. The objective of this study was to identify risk factors for clinically‐relevant postoperative pancreatic fistula (CR‐POPF) that are routinely available in the preoperative setting. Methods Preoperatively available variables for all pancreaticoduodenectomies from 2014‐2017 were examined using a national clinical registry. The cohort was separated into risk factor identification and internal validation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 28 publications
(61 reference statements)
3
49
0
9
Order By: Relevance
“…Despite advantages in surgical technique, perioperative care, centralization and introduction of enhanced recovery programme, the incidence of POPF remains unaltered [ 9 ]. The incidence of POPF of 10% in this Swedish study is in concordance with or even below international figures, 11.1–16.7% [ 18 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite advantages in surgical technique, perioperative care, centralization and introduction of enhanced recovery programme, the incidence of POPF remains unaltered [ 9 ]. The incidence of POPF of 10% in this Swedish study is in concordance with or even below international figures, 11.1–16.7% [ 18 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Most of the findings in this study are not controversial and support previously published papers. Presence of diabetes and a preoperative biliary drainage are features described earlier related to a reduced risk of POPF [ 20 , 21 ] as well as tumour location and its correlation to POPF [ 4 , 18 , 22 ]. These are parameters associated with inflammation of the parenchyma or obstruction of the pancreatic duct, leading to pancreatic firmness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results were inconsistent. Some papers have demonstrated results that con icted with our outcomes 17,30,31 , while others suggested that DM was associated with neither negative nor positive predictors of POPF 32,33 . The various proportions of patients with type 2 DM in the studies might explain this 34 .…”
Section: Discussionmentioning
confidence: 87%
“…Generally, visceral fat is a major factor in uencing the technical di culty during abdominal surgery. It has been shown in several studies [15][16][17] that obese patients are associated with a higher rate of complications such as wound infection, anastomotic stula, and longer hospital stay. Recently, it was reported that a high amount of visceral fat was associated with a signi cantly higher rate of overall complications and pancreatic stula development after PD 15,18 .…”
Section: Discussionmentioning
confidence: 99%